Management information systems in higher learning institutes of Malaysia: An overview - Jais Jamilin; Rahman Zarina Abdul; Hamid Suhaila Abdul; Ibrahim Zailani; Yusoff Mohd.Zaliman Mohd; Hussain Hanafizan (2023)
In Malaysia, Management Information System (MIS) is growing rapidly in most of the higher learning institutions, in line with the Government encouragement to make information technology (IT) as a part of our lives. Thus, a survey was carried out to oversee the roles and application of MIS in the higher learning institutions of Malaysia: emphasizing on managerial roles in decision making. Decision-making consists of stages that can be described as intelligence, design, choice, and implementation. In our survey twelve higher learning institutions are used to help identify factors/ activities involved in the first stage of decision making i.e. intelligence. From the survey, it was found that managers of higher learning institutions play a vital role in the implementation of MIS to enables business objectives and improve its productivity. Any management decisions made about IT are critically important since it will determine the prosperity and survival of the organization.